A Case of Severe Septicemia Following Traditional Samoan Tattooing - Elegino-Steffens, Diane U (University Clinical, Education & Research Associate (UCERA), 2013)
Traditional Samoan tattoos, or tatau, are created by master tattooists, or tufuga ta tatau, and their assistants using multi-pointed handmade tools. These tools are used to tap tattoo pigment into the skin, usually over several days. This traditional process is considered an honor to the one receiving the tatau. Unfortunately, as it is typically practiced according to cultural traditions, the sanitary practices are less than ideal. There have been several reported cases of severe infection, sepsis, shock, and even death as a result of traditional Samoan tattoos. Although Hawai'i is the home of the second largest Samoan population in the United States, short of only American Samoa, literature review found no published case reports in this state. Presented is a case of a 46-year-old man, who, after undergoing a modified version of traditional Samoan tattooing for 5 days, was admitted to the intensive care unit with severe septic shock due to poly-microbial bacteremia with Group A Streptococcus and Methicillin-sensitive Staphylococcus Aureus. In addition, we will discuss the previously reported cases, mainly documented in New Zealand, and review some of the mandatory sanitary standards put into place there.